BODIPY‐Based Profluorescent Probes Containing Meso‐ and β‐Substituted Isoindoline Nitroxides. Issue 3 (2nd January 2017) - Allen, Jesse P.; Pfrunder, Michael C.; McMurtrie, John C.; Bottle, Steven E.; Blinco, James P.; Fairfull‐Smith, Kathryn E.
Abstract : BODIPY is a highly versatile fluorophore for biological imaging with a tunable fluorescence emission (500–800 nm) that overlaps the optically transparent window for tissue (600–1300 nm). Herein, we describe the synthesis of optically distinct BODIPY‐based profluorescent probes bearing meso ‐ and β‐substituted isoindoline nitroxides and their corresponding methoxyamine derivatives. These profluorescent nitroxide probes possess strongly suppressed fluorescence, which can be revealed upon reduction or reaction with other radicals. Examination of the pentafluorophenylhydrazine reduction of the prepared probes by using tandem electron paramagnetic resonance (EPR) and fluorescence spectroscopy demonstrated that the asymmetric bis‐β‐substituted probe9 ( λ em = 603 nm) was reduced the fastest; however, the greatest difference in fluorescence emission between the nitroxide and its reduced hydroxylamine analogue was observed for probe7 ( λ em = 570 nm). The significant difference in fluorescence output between the nitroxides and their corresponding diamagnetic derivatives makes these probes ideal tools for imaging reactive oxygen species in biological systems. Abstract : Profluorescent nitroxide probes bearing isoindoline nitroxides substituted at the meso or β positions of the BODIPY core were synthesised. Reduction of the probes to their corresponding hydroxylamine analogues revealed a substantial fluorescence increase which demonstrates their potential as tools for imaging reactive oxygen species in biological systems.